Multilevel computer-generated holograms for reconstructing 3-D images in combined optical-digital security devices - Girnyk, V.I.; Kostyukevych, S.O.; Shepeliavyi, P.Ye.; Kononov, A.V.; Borisov, I.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Computer-generated holograms (CGHs) integrated within combined optical-digital security devices (CO/DSDs) are described in this work. They can restore the monochrome and color 3D images in white light. To record them, the Electron Beam Lithography (EBL) is used. Our investigations on optimization of synthesis and recording the CO/DSDs with the integrated in it multilevel CGHs of 3D images possessed horizontal parallax only (HPO) are presented here. The CGH fabrication process is mainly composed of two parts: calculation of the interferogram data (ID) and their recording. Calculation of the ID is done as follows: firstly, the geometrical and optical constants of recording scheme and the object surface represented by the elemental self-radiating areas, are determined, secondly, the basic parameters accounting for discretization of ID in hologram plane is defined. The ID values can be derived by calculation of the necessary elemental object areas bipolar intensities sum. Next, over suitable quantization of ID, recording the rectangle data appropriate for EBL onto glass coated with non-organic photoresist based on As₄₀S₄₀Se₂₀ is performed. We have also investigated reciprocal influence of an optical part of the CO/DSD and a digital one.